Laparoscopic treatment of appendiceal abscess in children - Kun Yang; Yang Li; Guang-wei Gong; Graham Lamont (Elsevier, 2020)
Objective: To determine the role of laparoscopic surgery in the treatment of appendiceal abscess in children. Methods: Case reports and a literature review of laparoscopic treatment of appendiceal abscess. Results: In a two-year period, three children were diagnosed with appendiceal abscess presenting as abdominal or fever symptoms, and were treated by laparoscopic surgery. There were two girls and one boy. Mean operative time was 90 minutes (range, 60-120), and there were nopostoperative complications. Conclusion: Laparoscopy is an effective and safe minimally invasive technique in the management of nocomplicated appendicitis. It is effective even in cases of appendiceal abscess.